Proses Penyelesaian Perkara Jual Beli Tanah (Studi Kasus di Pengadilan Negeri Klaten) - Mustofa, Jazzari Azis, Nuswardhani, S.H, S.U, Darsono, S.H, M.H (2016)
Land is natural resources which human really need to fullful their basic need,either it is for activity like cultivation or for dwelling, or for other infrastructure. There are various means to acquire the land, one of them is buying and selling. Through it, the land ownership is transferred from one party to another. This research uses descriptive normative approach, with primary and secondary data. They are collected through the study of literature, documentation, questionnaires and interviews by using qualitative data analysis. Based on the results of research and discussion, the assumption is that the conflict of land contract can be resolved through the district court. The litigants live in Klaten city.